GENDER ISSUES IN CHARLOTTE BRONTE’S JANE EYRE - Indah Miftah Awaliah (ETERNAL (English, Teaching, Learning and Research Journal), 2017)
The aim of this research is to explore gender issues reflected in Jane Eyre written by Charlotte Bronte. Jane Eyre centers woman as the second sex under the domination of men. Woman autonomy is part of gender issues which becomes a concern of feminist. Descriptive qualitative method through library research was used in this research by applying a feminist literary approach. Through this approach, women issues were digged out. The data were collected from primary data and secondary data. Primary data are collected from the novel Jane Eyre by Charlotte Bronte, while secondary data are collected from books and journals that related to the topic. The result of the research shows that gender issues in the novel did exist and were reflected both through male and female characters and through classification of gender manifestation of woman and men.